De novo Creation and Assessment of a Prognostic Fat-Age-Inflammation Index “FAIN” in Patients With Cancer: A Multicenter Cohort Study - Yin, Liangyu; Song, Chunhua; Cui, Jiuwei; Lin, Xin; Li, Na; Fan, Yang; Zhang, Ling; Liu, Jie; Chong, Feifei; Wang, Chang; Liang, Tingting; Liu, Xiangliang; et al. (Frontiers in Nutrition, 2022)
Background and aims: Malnutrition is highly prevalent and is related to multiple impaired clinical outcomes in cancer patients. This study aimed to de novo create an objective, nutrition-related index specially for prognostic purposes in oncology populations. Methods: We performed a multicenter cohort study including 14134 cancer patients. The prognostic impact for each baseline characteristic was estimated by calculating Harrell’s C-index. The optimal parameters reflecting the anthropometric, demographic, inflammatory and nutritional impact on patients’ overall survival were selected to develop the fat-age-inflammation-nutrition (FAIN) index. The associations of the FAIN with the nutritional status, physical performance, quality of life, short-term outcomes and mortality of patients were comprehensively evaluated. Independent external validation was performed to further assess the prognostic value of the FAIN. Results: The study enrolled 7468 men and 6666 women with a median age of 57 years and a median follow-up of 42 months. The FAIN index was defined as: (TSF + albumin) / [age + 5 × (neutrophil count / lymphocyte count)]. There were significant associations of the FAIN with the nutritional status, physical performance, quality of life and short-term outcomes. The FAIN also showed better discrimination performance than the Nutritional Risk Index, the Prognostic Nutritional Index and the Controlling Nutritional Status index (all P < 0.05). In multivariable-adjusted models, the FAIN was independently associated with a reduced death hazard both as a continuous variable (HR = 0.57, 95%CI = 0.47 to 0.68) and per one standard deviation (HR = 0.83, 95%CI = 0.78 to 0.88). External validation in a multicenter lung cancer cohort (n = 227) further confirmed the prognostic value of the FAIN. Conclusions: This study created and assessed the prognostic FAIN index, which might act as a feasible option to monitor the nutritional status and help develop intervention strategies to optimize the survival outcomes of cancer patients.